Vers une théorie et une méthode d’évaluation de l’utilisabilité des systèmes complexes homme-technologie - Leena Norros; Paula Savioja (Activités)
One of the central roles of ergonomic research is to provide a normative basis for the evaluation of the appropriateness of artefacts used in various human activities. In this paper a new activity theory based approach, the Core-Task Analysis is introduced. Inspired by that, an evaluation method, Contextual Assessment of Systems Usability, was developed for the analysis of the appropriateness of complex information and control systems. The basic structure of the method is described and the indicators for assessment briefly described.